Uji Bioaktivitas Fraksi Etanol Ekstrak Kulit Buah Jeruk Purut Citrus hystrix Sebagai Anti Bakteri Staphilococus aureus dan Escherecia coli - Alif Rahman Habibi; Alya Rahmaditya Arfan; Rini Susanti; Reynaldi Dwi Gustiansyah (CV. ALIM'SPUBLISHING, 2024)
Plants have several ways to protect themselves from bacteria, one of which is by producing compounds that are toxic or repellent to bacteria. Compounds produced by plants are known as secondary metabolite compounds which originate from secondary metabolic processes. Several secondary metabolite compounds such as flavonoids, alkaloids, saponins, tannins, steroids and terpenoids are currently widely used as antibacterials. One of the plants that has the potential to be developed as a herbal medicine is kaffir lime leaves. Citrus hystrix is ​​the part of the plant most often used by the public. Both for cooking and traditional medicine purposes. In this research, it is hoped that lime peel extract can act as an antibacterial for Escherichia coli and staphylococcus aereus, so that it can be used as a herbal plant for diseases caused by these two bacteria. In the research, the concentrations used for each test bacteria were 50%; 25%; 12.5%. in observing S. aureus bacteria 1x24 hours with a concentration of 50%, the size of the inhibitory zone was 16 mm, the 25% concentration was 11 mm and the 12.5% ​​concentration was 9 mm. Meanwhile, E. Coli bacteria did not show any reaction to the heruk peel extract.